Human movement influenced by perceived risk of wildlife encounters at fine scales: Evidence from central India. (February 2021) - Read, Daniel J.; Habib, Bilal; Stabach, Jared; Leimgruber, Peter
Abstract: Most research applying the 'landscape of fear' concept to human-wildlife interactions explores wildlife responses to anthropogenic risks, such as altered movement patterns. Here, we explored people's landscapes of fear by investigating their perceptions of spatio-temporal variation in the risk of encountering wildlife, and how those perceptions influence their movement. We conducted a participatory risk mapping exercise with people living in the buffer zones of two protected areas in central India, which provide habitat to tigers, leopards, sloth bears, and numerous crop-raiding herbivores. We then tracked people's movement using GPS devices and explored how their movement related to their risk maps. Results of integrated step selection functions show that perceived risk influenced the speed and directedness with which people move, mixed evidence that perceived risk influenced where people went (habitat selection), and variation in how individuals responded to risks from different species. Future research on how humans and wildlife adapt to each other should investigate (1) human behavioral responses to wildlife over longer periods of time, (2) how movement affects the spatial patterns of human-wildlife conflict, and (3) the cultural and cognitive dimensions of how risk and emotions influence people's movement decisions. Highlights: Mutual behavioral adaptations facilitate human-wildlife coexistence. We measured how perceived risks from wildlife influence people's movement. Agreement among people's spatio-temporal perceptions of risk varied with species. Perceived risk influenced speed and directedness of movement. Understanding human movement can advance efforts to promote coexistence.